`Managing for outcomes': accountability and thrust - Baehler, Karen (2003)
Central agencies in New Zealand are now defining public management performance to include both the quality of a manager's `account' of output-outcome links and the manager's record of delivering efficient outputs. This article: (1) argues that the hard edge of accountability for deliverables must be dulled somewhat in order to pursue outcomes more vigorously; (2) shows how managers can use evaluation tools known as theories-in-action or logic models to give accounts of policy and management thrust; (3) proposes preliminary performance criteria for outcomes-focused management; and (4) attempts to sketch a new `managing for outcomes' accountability bargain. The conclusions apply broadly to any jurisdiction interested in holding managers accountable for outcomes-focused management. - Reproduced.
Keywords: Public administration